KOMPETENSI PROFESIONAL GURU YANG BERSERTIFIKASI DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA - Endang Pristiawaty (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
Essential competencies professorship is professional competence, social competence, and personal competence. Professional competency, competence in the field of substance or field of study,  competence  areas  of  learning,  teaching  methods,  assessment  systems,  the  value  of education and guidance. Social competence, competence in the field of relationship and service, community  service.  Personal  competence,  competence  value  built  through  behaviors  that teachers, has a personal and attractive appearance, impressive and teachers slang and "funky." The teacher called to be willing to learn how to teach well and fun learners and called to find a way of learning right. Let's just say, a teacher is not only a profession that is determined through testing  and  certification  competence  alone,  but  involves  the  heart,  meaning  that  from  the beginning  they  had  dreams  of  becoming  a  teacher,  a  teacher  who  knew  him,  and  as  a  noble humanitarian duty calls followed by awards professional as well.Seritifikasi teacher is an attempt to improve the quality of teachers is accompanied by an increase in the welfare of teachers, which is expected to improve the quality of learning and the quality of education in Indonesia on an ongoing basis.Key Words : Professionals, Teachers competence, and Certification